Hospital admissions, outpatient visits and healthcare costs of community‐dwellers with Alzheimer's disease. Issue 8 (10th December 2014) - Tolppanen, Anna‐Maija; Taipale, Heidi; Purmonen, Timo; Koponen, Marjaana; Soininen, Hilkka; Hartikainen, Sirpa
Abstract: Background: Detailed data on the health care service use of people with Alzheimer's disease (AD) are scarce. Methods: We assessed the health care service use of all community‐dwelling persons with clinically verified AD diagnosis, residing in Finland on December 31, 2005 (n = 27, 948) in comparison to matched cohort without AD. Hospitalization data during 2006–2009 were extracted from the National Hospital Discharge Register. Results: Comorbidity‐adjusted incidence rate ratios; IRR (95% CI) were 1.25 (1.22–1.28) for inpatient admissions and 0.72 (0.68–0.77) for outpatient visits. People with AD had more general health care admissions (IRR, 95%CI 1.73, 1.67–1.80) but less admissions to specialty units 0.82 (0.79–0.85) than the non‐AD group, with psychiatry being the only specialty with more admissions in the AD group. People with AD had 16 more hospital days/person‐year. Conclusions: It would be important to assess whether inpatient hospitalizations of AD patients could be decreased by better targeting of outpatient services and whether other conditions are underdiagnosed or undertreated among persons with AD.